Cost-to-serve: a strategic tool for decision making in hotel industry using fuzzy technique. (2017) - Parkhi, Shilpa; Patil, Sandeep; Sharma, Ayush
This paper aims to assess the usefulness of cost-to-serve as a strategic tool for customer profitability management through literature review, comparison with traditional measure (such as contribution), a survey in hotel industry and use of fuzzy evaluation method to understand factors affecting total cost-to-serve. The study presents literature review related to cost-to-serve, customer profitability, product profitability, super variable expenses, classification of offerings based on customer, fuzzy evaluation and a survey on hotel industry. The literature review demonstrates that some studies have emphasised on the power of cost-to-serve as a tool and fuzzy evaluation techniques have been used in multi-criteria analysis. The findings of the study show how offerings can be classified based on customers, the cost incurred on each offering can be ranked and profitability can be analysed and the impact that each expenditure can have on each offering. Results based on surveys done in a single region cannot be generalised to other regions. This paper includes a comprehensive literature review on cost-to-serve and contains valuable information about various costs in hotel industry collected through surveys. It also offers additional insights into use of fuzzy evaluation techniques for understanding cost-to-serve a particular set of customers.